Reducing Repeat Sexual Assault Victimization: Design and Testing of a Risk Reduction Program in New York City, New York, and Seattle, Washington, 2003-2005 - Davis, Robert C. ([Verlag nicht ermittelbar], 2011)
The goal of the study was to develop an intervention that would be analogous to safety planning for battered women, and one that could be used by sexual assault counselors as an adjunct to psychological counseling. The project was conducted at Safe Horizon in New York City and at Harborview Medical Center in Seattle from August 2003 to May 2005. The client populations of the two programs were complementary. Safe Horizon's clients were primarily Black (36 percent) and Latina (26 percent). In contrast, a majority of Harborview clients were White (59 percent), although Harborview also had many non-White, non-Hispanic clients. Approximately half of the eligible candidates were randomly assigned to participate in a four-hour workshop on avoiding sexual assault while the others were assigned to a control condition that did not receive the training. Both groups participated in a baseline assessment battery administered in person. After completion of the assessment, those assigned to the experimental condition began the workshop. Researchers contacted women in both groups six months later for a second assessment, this time conducted over the phone. The 14 data files contain information related to alcohol consumption, tonic immobility, knowledge of sexual assault risk factors, attributions for the most recent sexual assault, self-efficacy, risky behaviors, post-traumatic stress disorder (PTSD) symptomology, and sexual victimization. The data also contain one file with demographic information. Each data file contains 84 cases. Across all parts, the data collection has 612 variables.